Reducing long acting antipsychotic injection dosage frequency: A pilot study in a community mental health team. (2nd January 2021) - Fleming, D.; Raynsford, J.; Hosalli, P.
Abstract: Background: Antipsychotic long acting injections (LAI) allow a range of dosage intervals to be administered. Short intervals can be inconvenient for patients and staff. There are few clinical reasons for using them yet this is common practice. Aims: This study aimed to examine the feasibility of reducing LAI frequency with service user consent. Methods: The study took place in a community mental health team in the north of England. A specialist mental health pharmacist reviewed records of all service users on LAI and drew up an action plan. Each service user then met with the consultant psychiatrist for medication review. Result: Nineteen out of thirty service users on LAI had intervals less than the maximum licensed. The frequency was reduced in eight cases. After 6 months follow–up, there was no deterioration in symptoms. In nine cases, antipsychotic doses were also reduced as a result of the review. Conclusion: Where a service user is prescribed a LAI with a short dosage interval consideration should be given to increase the interval. This can free up service user and staff time. A medication focused review can also lead to other benefits such as dosage reduction.